2020
DOI: 10.1111/jssr.12696
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Religious Motivation Influence How People Think

Abstract: Motives matter and may have implications for how people cognitively experience meaning through religion and spirituality. Specifically, intrinsically motivated people perceive religion and spirituality are more central to meaning in life, which should promote a tendency to adopt more coherent, expansive cognitive representations. In contrast, extrinsically motivated people may adopt narrower cognitive representations since their motivation is more proximally oriented. The present study tests these possibilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The findings of this research show that as Michaels, Petrino, and Pitre‐Zampol (2021) stated, people's motivations and goals for participating in a religious event can be internal or external. However, one of the biggest differences between this research and the literature is considering the structural environment inside the country as a reason for pilgrims to participate in religious events.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The findings of this research show that as Michaels, Petrino, and Pitre‐Zampol (2021) stated, people's motivations and goals for participating in a religious event can be internal or external. However, one of the biggest differences between this research and the literature is considering the structural environment inside the country as a reason for pilgrims to participate in religious events.…”
Section: Discussionmentioning
confidence: 64%
“…In contemporary literature, religious pilgrimage and religious tourism are considered as a subset of modern pilgrimage; a religiously motivated trip to a sacred place that can include natural elements, religious sites, religious activities, and rituals or festivals (Raj and Morpeth 2007; Sharpley 2009). Michaels, Petrino, and Pitre‐Zampol (2021) state that people's motivations are very substantial and may have consequences for how people's cognitive experience through religion and spirituality. Intrinsically motivated individuals view religion and spirituality as more important to meaning in life, which should foster a tendency to adopt more coherent and expansive cognitive representations.…”
Section: Research Literaturementioning
confidence: 99%
“…In fact, HIMRS measures a single crucial dimension: ultimate versus instrumental religious motivation. Michaels et al (2021) found that among religious people, intrinsic and extrinsic-personal religious motivations indirectly influence high-level action identification through strength of spiritual beliefs. Besides, extrinsic-social religious motivation and religious service attendance did not relate to action identification, demonstrating that "religious motivation differences are consequential for the action identities people rely upon to form a sense of meaning" (p. 64).…”
Section: Introductionmentioning
confidence: 99%